OMNICHANNEL APPROACH: CUSTOMER LOYALTY THROUGH BRAND EXPERIENCE AND CHANGE HABITS CUSTOMER ON SEPHORA - Desak Made Febri Purnamasari; Ida Ayu Oka Martini; Lingga Aqila Maharani; Ida Ayu Iswari Pidada (Media Bina Ilmiah, 2022)
Omnichannel Approach: Customer Loyality Through Brand Experience and Change Habits Customer on Sephora Kuta, the purpose of this study was to examine the effect of the omnichannel approach on customer loyalty through brand experience and change habits of customers on Kuta. Thus, this study determines the structural causal relationship between the omnichannel approach and one dependent variable and two mediating variables. A total of 100 respondents who are customers of Kuta Kuta responded to the questionnaire. This study uses partial least square (PLS) and reveals the results that the omnichannel approach has a positive effect on customer brand experience; the omnichannel approach positively affects change habits of customers; brand experiences that arise positively affect customer loyalty; change habits of customers positively affect customer loyalty; The omnichannel approach does not become a fulcrum for customers to be loyal so that the results obtained in the field are negative; The omnichannel approach has a positive effect on customer loyalty through brand experience and change habits. The results of this study indicate that customer brand experience and change habits have an important effect on the omnichannel approach to increasing customer loyalty.